Tingkat Kepuasan Pasien Terhadap Pelayanan Kefarmasian di Puskesmas Oebobo Kota Kupang - Ni Nyoman Yuliani; Anita Rae; Maria Hilaria; Marce Takubessi (Jurnal Inovasi Kebijakan, 2020)
. Pharmaceutical services are integrated activities to identify, prevent and resolve problems related to drugs. Patient satisfaction is a level of satisfaction that arises as a result of the health service performance obtained after the patient has compared it with what he expected. This research was conducted with the aim of knowing the level of patient satisfaction with pharmaceutical services at the Oebobo Health Center in March - April 2018. This type of research is a non-experimental study with a descriptive design (survey research), the type of research is purposive sampling using a questionnaire sheet as a research instrument, then the average percentage of patient satisfaction was calculated and classified. Data analysis of the results of research conducted by researchers on 345 respondents showed that the level of patient satisfaction with each variable was: 84% reliability, 85% responsiveness, 86% confidence, 85% empathy and 82% performance variables, thus, on average Level of Patient Satisfaction with Pharmaceutical Services at Oebobo Community Health Center, Kupang City March-April 2018 as a whole is 84% with satisfaction classification, which is very satisfied.